Fantasy breakdown : a case study on organizational crisis communication and stakeholder reaction during mass product failure - Ruihley, Brody J. (SAGE Business Cases., 2018)
On the first Sunday of the National Football League's 2016–17 season, a technical issue caused ESPN's fantasy-football website and mobile application to fail. ESPN's product failure is no small problem and represented a major organizational crisis; with 7.1 million unique users, ESPN represents the largest provider of a multi-billion-dollar fantasy-sport industry. This case study examined ESPN's organizational communication strategy, as well as the stakeholder responses surrounding the failure of ESPN's fantasy-football website and application on the most anticipated day of the fantasy-sport season. Using content analysis and partnering with a social media data insights company, the study examined social media messages from both the organizational and consumer side of this fantasy-sport product failure. Through sampling 1,542 social media messages from a population of 11,881 unique comments via Twitter, the reactive nature of ESPN's messages and the direct responses from its consumers was ascertained.